GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
978-1-78118-441-7
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Comunicado: Conferência “Como está Moçambique?” - Instituto de Estudos Sociais e Económicos (IESE) (Instituto de Estudos Sociais e Económicos (IESE), 2018)
Veja e aceda ao comunicado subscrito pelas organizações da sociedade civil – Observatório do Meio Rural (OMR), Centro de Integridade Pública (CIP), Mecanismo de Apoio à Sociedade Civil (MASC) e Instituto de Estudos Sociais e Económicos (IESE), resultante da conferência “Como está Moçambique?”, que decorreu no dia 16 de Maio último, no Hotel Montebelo Indy, em Maputo. Leia o comunicado aqui.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil

Youth initiatives: Supporting citizen engagement with government and civic life - Orrnert, Anna (GSDRC, University of Birmingham, 2018)
There is a large volume of literature on youth participation in development, including on the benefits of involving young people in local, national, regional and global governance initiatives. Although not as voluminous, there is also a significant body of work on youth participation in civic life, though much of this focuses on issues of education and employment (Oxfam 2016) as well as health (particularly initiatives related to HIV/ AIDS). It was not possible to identify a large body of literature around more multi-faceted and holistic initiatives (for example, involving different themes and connecting at different levels).
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; youth / juventude

Afrobarometer Round 7. Summary of Results for Mozambique, 2018 - Ipsos Mozambique (Ipsos Mozambiqu, 2018)
Afrobarometer is a pan-African, non-partisan research network that conducts public attitude surveys on democracy, governance, economic conditions, and related issues in countries across Africa. Six rounds of surveys were conducted between 1999 and 2015, and Round 7 surveys are being carried out in 2016-2018. Afrobarometer conducts face-toface interviews in the language of the respondent’s choice with nationally representative samples of 1,200 or 2,400 respondents. Afrobarometer is produced collaboratively by social scientists from across Africa. Coordination is provided by the Center for Democratic Development (CDD) in Ghana, the Institute for Justice and Reconciliation (IJR) in South Africa, the Institute for Development Studies (IDS) at the University of Nairobi in Kenya, and the Institute for Empirical Research in Political Economy/School of African Economics (IERPE/ASE) in Benin. Michigan State University (MSU) and the University of Cape Town (UCT) provide technical support to the network.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

GFF Implementation Plan for the Gff Civil Society Engagment Strategy - Global Financing Facility (Global Financing Facility, 2017)
The implementation plan for the civil society engagement strategy (CSES) is developed to provide civil society organizations in countries (CSOs) with an operational framework to strengthen their engagement in the GFF process with a view to supporting the achievement of the objectives of the GFF and national investment cases. The plan reflects and builds on, and should be read in conjunction with the CSES. It is shaped and informed by GFF country implementation experiences to date, 12345 as well as the results of a targeted 2017 survey sent to CSOs working in GFF countries. The survey was geared towards understanding: 1) the civil society landscape in countries; 2) the level of knowledge of the GFF processes by CS; 3) priority actions CS can take to strengthen their engagement in the GFF processes and to support the achievement of the RMNCAH investment cases; and 4) what resources CS might need to better engage with national platforms and planning processes and to implement the identified supportive actions. The survey was sent to 18 organizations in 12 GFF countries and had a 61% response rate.
Sixth Invertors Group Meeting
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; health / saúde

Parte IV - Eleições, Governação Local e Sociedade Civil - Brito, Luís de; Chivulele, Fernanda Massarongo (Economia, Recursos Naturais, Pobreza e Política em Moçambique - Uma colectânea de textos, 2017)
IDeIAS Nº2 Uma nota sobre o recenseamento eleitoral IDeIAS Nº5 Beira – o im da Renamo? IDeIAS Nº6 Sem surpresas: abstenção continua maior força política na reserva em Moçambique … até quando? IDeIAS Nº8 Sobre os votos nulos IDeIAS Nº20 Sobre a transparência eleitoral IDeIAS Nº22 Uma análise preliminar das eleições de 2009 IDeIAS Nº48 Sobre resultados eleitorais e dinâmica eleitoral em Sofala IDeIAS Nº50 Uma relexão sobre o calendário e o recenseamento eleitoral para as eleições autárquicas de 2013 IDeIAS Nº38 Comissão Nacional de Eleições: uma reforma necessária IDeIAS Nº83 Rever o sistema eleitoral IDeIAS Nº3 Orçamento participativo: um instrumento da democracia participativa IDeIAS Nº16 A primeira reforma iscal autárquica em Moçambique IDeIAS Nº18 Relexões sobre parcerias público-privadas no inanciamento de governos locais IDeIAS Nº21 Pequenos provedores de serviços e remoção de resíduos sólidos em Maputo IDeIAS Nº41 Estado e informalidade: como evitar a “tragédia dos comuns” em Maputo? IDeIAS Nº66 Reformas de descentralização e serviços públicos agrários em Moçambique: porquê persistem os desaios? IDeIAS Nº70 Autonomização local para quê? Questões económicas no debate sobre autonomia local IDeIAS Nº24 Sociedade civil em Moçambique e no mundo IDeIAS Nº27 Sociedade civil e monitoria do orçamento público IDeIAS Nº58 As “revoltas do pão” de 2008 e 2010 na imprensa IDeIAS Nº61 Indignai-vos! IDeIAS Nº19 “O inimigo é o modelo”! Breve leitura do discurso político da Renamo IDeIAS Nº62 Media e campanhas eleitorais
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; governance / governação

Avaliacao Nacional sobre o Ambiente Propício para Actuação das OSC: O caso de Moçambique - Francisco, Albino (Joint - Liga de ONGs em Moçambique, 2017)
O presente relatório apresenta as principais constatações resultantes de um estudo realizado em Moçambique pela JOINT – Liga de ONGs em Moçambique, com o objectivo de fornecer uma caracterização do ambiente propício para a intervenção da Sociedade Civil no país. O estudo é parte das Avaliações Nacionais sobre o Ambiente Propício (EENA), uma metodologia de pesquisa juntamente desenvolvida pela CIVUS e ICNL, no âmbito da Iniciativa de Espaço Cívico. As avaliações EENA estão sendo implementadas em 16 países, ao longo dos últimos dois anos, um dos quais Moçambique. Este estudo, designado “Avaliação Nacional sobre o Ambiente Propício para a Actuação (EENA)” das Organizações da Sociedade Civil (OSC) em Moçambique, avaliou o ambiente propício em sete dimensões, nomeadamente: (1) Formação; (2) Operação; (3) Acesso a Recursos; (4) Expressão; (5) Reunião Pacifica; (6) Relações entre o Governo e a Sociedade Civil; e (7) Tributação. Em geral, a principal constatação do estudo mostra que o ambiente propício para a actuação das OSC em Moçambique não é favorável, permanecendo sérios desafios que constrangem a intervenção das OSC aos diferentes níveis. A actual situação de instabilidade política e militar, e de grave crise económica e financeira, tem resvalado para situações de intolerância política e limitações ao exercício das liberdades fundamentais por parte dos cidadãos, situação que concorre para tornar mais complexo o ambiente de actuação das OSC no país. O estudo conclui que, com base na análise do quadro legal e da percepção sobre a sua prática, permanecem sérios desafios na intervenção das OSC em Moçambique. Embora em algumas dimensões o ambiente legal e prático é mais favorável do que em outras, em geral o ambiente não pode ser considerado propício, recomendando: - A revisão da Lei 8/91, a Lei das Associações, adequando-a aos actuais desafios de desenvolvimento das OSC e do país de forma a permitir o acesso simplificado ao registo a todos os níveis e facilitar a operação efectiva das OSC; - A criação de uma arquitectura de financiamento mais equitativa para as OSC, que alivie a dependência dos fundos externos e permita o acesso aos fundos públicos internos; - Tornar a legislação em vigor sobre a liberdade de expressão e de reunião pacífica efectivamente conhecida e implementada em conformidade, garantindo o respeito pelos direitos dos cidadãos e das OSC em geral; - A criação de um ambiente político que garanta a participação efectiva das OSC nos processos de governação aos diferentes níveis; - Estabelecimento de um sistema tributário mais justo e adequado ao contexto real de operação das OSC em Moçambique
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil

Civil society organisations’ political control over Brazil and Japan’s development cooperation in Mozambique: More than a mere whim? - Chichava, Sérgio; Durán, Jimena (LSE, 2016)
This article aims to analyse and explain the reasons behind the CSOs’ strong criticism of the ProSavana programme. This will contribute toward: (1) understanding the role of Mozambican CSOs as actors regulating international development cooperation projects; (2) revealing the political and economic interests behind ProSavana, as a first step toward a more critical approach to trilateral cooperation; and (3) illustrating through this case how a partnership between Brazil and “traditional” donors actually works. Firstly, we will analyse the cooperation policies of Brazil and Japan in Mozambique, taking into account its evolution, actors, mechanisms and motives. Secondly, we will introduce ProSavana, examining the narratives and roles of Japan and Brazil in this programme. Thirdly, we will consider the engagement of CSOs from the three countries, their role in exerting a political check on the Brazilian and Japanese governments, investors, and companies, as well as their narratives and mechanisms of protest.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; civil society / sociedade civil; development partners / parceiros de cooperação

Corporate Social Responsibility in Mozambique - Kaufmann, Friedrich; Simons-Kaufmann, Claudia (Corporate Social Responsibility in Sub-Saharan Africa: Sustainable Development in its Embryonic Form, 2016)
Mozambique is a young African country with a strong growing economy and increasing foreign direct investment. We can observe a rising number of Corporate Social Responsibility (CSR) projects and activities in the country. Nevertheless there is still no systematic approach or coordination through public authorities or the business sector itself. CSR is mainly motivated by immediate own company needs like training or health of workers. We also find philanthropy projects as well as projects supporting local communities on development priorities, mainly health, education and community development. CSR, as part of a business concept, is mainly limited to large companies and foreign investors with international experience and less to small and medium-sized enterprises (SMEs). Many national companies, especially SMEs still do not have the CSR capacity or the respective mind set. First of all it is the mega projects that have their professional CSR departments and budgets. In the mining sector a CSR component is now compulsory by law since 2014.As public institutions are weak, CSR in Mozambique is more about “CSR towards compliance” and sometimes less about “CSR beyond compliance”. Strong views are expressed by civil society that for example the enforcement of labour legislation within companies is weak and hardly controllable by the government. This fact combined with corruption issues makes CSR towards compliance of existing labour, environmental, fiscal laws and other regulation an important topic. Nevertheless it is questionable if this should be considered as CSR. CSR in general is sometimes seen as “green washing” by big investors, benefitting on the other hand from generous tax exemptions and special deals with the government. Nevertheless, CSR is of growing importance in Mozambique and as the new mining CSR law shows, government is slowly entering the CSR landscape. A better coordination and public-private dialogue about CSR is necessary in order to make it a more useful and an efficient instrument for development. Nevertheless it should be clear that CSR is voluntary and in a globalized economy with international value chains becomes more and more an international issue.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado

EU & Partners' Country Roadmap for Engagement with Civil Society: 2016-2019 - Government of Canada; Government of Switzerland; UNICEF; USAID (Governments of Canada, Switzerland, UNICEF, USAID, 2015)
Study commissioned by EU and other countries on CSO engagement. The identification of priorities is based on four criteria: • The findings of the recent mapping of civil society in Mozambique commissioned by the EU and other studies; • The official EU guidance on the preparation of a civil society roadmap; • Existing and planned EU interventions and of the partners engaged in the roadmap; • The need to combine a longer term perspective with concrete actions over the next 3 years. The priorities constitute primarily a common agenda that will shape and orient discussions and collaboration between the roadmap partners. It allows situating individual interventions in a broader collective framework and as such adds a strategic dimension to programming.
Keywords: #Policy Document / Documento de Política; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação

Relatório do Estudo sobre a Sustentabilidade das Organizações da Sociedade Civil (versão final) - Eurosis (Eurosis, 2015)
O presente documento constitui o Relatório do Estudo de Sustentabilidade das Organizações da Sociedade Civil solicitado por 5 Organizações Não Governamentais (DIAKONIA, FHI360, HELVETAS, KEPA e OXFAM NOVIB) e realizado pela EUROSIS Consultoria e Formação em Gestão. De forma sintetizada, este estudo tinha como objectivos chave: a) mapear o entendimento que a governação e gestão das OSC têm sobre sustentabilidade e seus desafios; b) ajudar a desconstruir a percepção que limita a sustentabilidade à viabilidade económico-financeira das OSC, trazendo à superfície outras dimensões também relevantes para o efeito; c) recomendar acções para a tomada de decisão dos diversos actores que trabalham no fortalecimento das OSC. Tendo em consideração os seus objectivos, este estudo está estruturado em quatro componentes chave: • revisão de literatura internacional para identificação de factores que, de acordo com pesquisa internacional, influenciam sustentabilidade de OSC. • recolha de dados (através de questionários auto-administrados, entrevistas face-a-face e workshops) para o levantamento de percepções e opiniões de OSC com relação ao conceito de sustentabilidade, limitantes colocadas pelo contexto moçambicano à sustentabilidade de OSC, fragilidades das próprias OSC que não ajudam à sustentabilidade). Importa referenciar que para a recolha de dados: 79 representantes de 62 OSC preencheram o questionário online; foram realizadas 19 entrevistas semiestruturadas e em profundidade; e foram realizados três workshops em Maputo, Chimoio e Nampula com a participação de 69 representantes de 54 OSC. • análise e conclusões que incluiu: a) comparação dos factores mencionados em literatura internacional com os mencionados pelos respondentes no estudo para identificação de factores comuns e identificação daqueles que não parecem estar no campo das preocupações ou prioridades da maior parte das OSC respondentes; b) tendo em consideração a comparação anterior, elaboração de proposições sobre os factores que, na nossa opinião, afectam ou limitam a sustentabilidade de OSC em Moçambique. • recomendações elaboradas com base na análise e nas conclusões apresentadas
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil

Mapping study of Civil Society Organisations in Mozambique - Topsøe-Jensen, Bente; Pisco, Alice; Salimo, Padil; Lameiras, João (ALTAIR Asesores and Agriconsulting. S.L, 2015)
The Mapping Study of Civil Society Organizations (CSOs) in Mozambique was carried out during the first half of 2015, within the context of preparation for the Roadmap of the European Union (EU), Member States and other partners for engagement with civil society. Data collection included document analysis, and interviews with CSOs, international partners and Mozambican government institutions at national, provincial, district and local level. In the first phase of the field work, nine provincial workshops were held, and in the second phase four workshops were held for verification of findings and validation of recommendations. The overall objective of the mapping study is to provide the EU and all interested parties with a comprehensive overview of the state of CSOs in Mozambique, including identification of their needs and proposals for maximizing their influence in the definition and monitoring of public policies. The study also presents recommendations on the priorities to include in the EU Roadmap for engagement with civil society, and may thus contribute to improving the strategy for support to CSOs within current programming. The specific objectives are to: - Analyse the global state of play of the civil society in Mozambique, particularly regarding the environment, structure, capacity, engagement and sustainability of its organizations; - Identify existing the gaps, the fundamental needs and the opportunities for the CSOs to get involved in and influence policy processes, to monitor implementation of state commitments, and in general to claim transparency in public processes and good governance; - Provide specific recommendations on how to better meet needs identified by suggesting priorities and actions for programmes and other civil society support interventions.
Keywords: G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil

Mid-Term Review of the AGIR Programme. Final report. - Kelpin; Johnsen, Vibe; Macuane, José Jaime; Christoplos, Ian; Rothman, Jessica (Sida, 2013)
This mid-term review report of the ‘Action Programme for Inclusive and Responsible Governance’ (AGIR) in Mozambique was carried out from August 2012 to its completion at the end of October 2012 by a three-member review team fielded by Indevelop. A presentation of the preliminary findings was made on October 24th, 2012 to AGIR intermediaries and AGIR CSO partners. Subsequent to this presentation, the review team was provided with the just-completed 2012 semi-annual report, which was written and submitted jointly by AGIR intermediary organisations. AGIR has duration of five years beginning in 2010 and ending in 2014. Sweden is the only core donor, with Denmark and the Netherlands also providing support to participating INGOs (International Non-Governmental Organisations). The programme works with both national partners and with organisations in the provinces. In an effort to strengthen civil society and civil society organisations within Mozambique, the Swedish Embassy initiated the AGIR programme in 2010. The objective of AGIR is to: Support Mozambican civil society organisations, strengthening their capacity for and impact on improving transparency, accountability, citizen’s participation, access to information, respect for human rights, and gender equality. In line with the Paris Declaration and the Accra Agenda for Action, AGIR is structured to provide “good donor-ship” through support given for CSO ‘core funding’ that is aligned with the “strategic direction of the organisation” and to support and facilitate linkages and knowledge sharing between Mozambican CSOs.2 The main support modality for this capacity strengthening of CSOs is to “work through a limited number of qualified intermediary organisations within the following four clusters of support: i) Participation, social and legal accountability, including monitoring of respect for human rights; ii) Social accountability in management of natural resources and community land rights; iii) Transparency, financial and political accountability; and, iv) Promotion of access to information.”
Keywords: G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil

Support to Civil Society Engagement in Policy Dialogue - Ministry of Foreign Affairs of Denmark (SIDA, 2013)
This evaluation, the ‘Joint Evaluation of Support to Civil Society Engagement in Policy Dialogue’ was initiated by the Donor Group on Civil Society and Aid Effectiveness. Specifically it was commissioned by three Development Partners (DPs), ADC/Austria, Danida/Denmark and Sida/Sweden, which form the Management Group. A larger group of bilateral DPs support the evaluation through their participation as the international Reference Group. The evaluation took place between June 2011 and September 2012. The Evaluation Team was drawn from the consulting firm ITAD Ltd in the UK (lead firm), together with experts from COWI (Denmark) and experts from each of the three countries selected for the fieldwork, Bangladesh, Mozambique and Uganda. The purpose of this evaluation is lesson learning, to help DPs gain a better understanding of how best to support Civil Society Organisations (CSOs) in the area of policy dialogue. The findings will also have direct relevance to the CSOs in the three countries and the wider CSO community, as well as the Governments and local authorities interacting with Civil Society (CS) representatives. The evaluation focuses on: 1. How CSOs engage in policy dialogue and the relevance and effectiveness of their policy work; 2. the enabling environment, that is the enablers and barriers to CSO engagement; and 3. how different DP support strategies may influence CSOs’ ability to engage in policy dialogue, and how best the DPs might support CSO policy dialogue in the future.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; civil society / sociedade civil

Avaliação Conjunta do: Apoio à Participação da Sociedade Civil no Diálogo sobre Políticas - ITAD; COWI (ITAD/COWI, 2012)
Estudo de Caso 1. Planificação Distrital e Monitoria do Orçamento Planificação Distrital e Monitoria do Orçamento são processos interligados mas distintos. A Planificação Distrital é um processo de política ao abrigo da LOLE1, segundo a qual a participação das comunidades locais é um princípio básico na governação local e gestão de bens públicos. A planificação distrital é um processo simples, no qual a sociedade civil (SC) local é representada através dos Conselhos Consultivos Locais. O processo de planificação é muitas vezes uma “lista de compras”, sem ligação com a definição de prioridades do orçamento, que é feita ao nível do governo central ou provincial, muitas vezes depois de a planificação ter sido feita a nível distrital. A monitoria sistemática do orçamento é um exercício recente em Moçambique, embora tenha já sido feita sob os auspícios de várias projectos apoiados por Organizações Internacionais da Sociedade Civil (OISCs). Baseia-se na experiência da SC em vários mecanismos de diálogo sobre políticas (por exemplo, Observatórios de Desenvolvimento (ODs)). Estudo de Caso 2. Legislação sobre Violência Doméstica A violência contra a mulher (VCM), em geral, e a violência doméstica contra as mulheres, em particular, constituem um problema global. Em Moçambique, é uma prática generalizada e, infelizmente, largamente aceite, que assenta em sólidos papéis tradicionais de género. Isto é testemunhado por estudos e casos documentados recolhidos por OSCs (WLSA, Le Musica), e por estatísticas dos Gabinetes de Atendimento para mulheres vítimas de violência37. Os casos de violência doméstica contra as mulheres eram, porém, vistos como pertencendo à esfera doméstica (privada) e, assim sendo, não eram considerados uma questão pública; e, até recentemente, não havia nenhum enquadramento jurídico da questão.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género

Afrobarometer Round 5. Summary of Results for Mozambique, 2012 - Centro de Pesquisas de Governação e Desenvolvimento (CPGD) (Centro de Pesquisas de Governação e Desenvolvimento (CPGD), 2012)
The Afrobarometer is a comparative series of public attitude surveys that will be covering up to 35 African countries in Round 5 (2011-2013). Based on representative national samples, the surveys assess citizen attitudes to democracy and governance, markets, and civil society, among other topics. The first round of surveys was conducted between 1999-2001 and covered seven Southern African countries (Botswana, Lesotho, Malawi, Namibia, South Africa, Zambia and Zimbabwe), three countries in West Africa (Ghana, Nigeria and Mali) and two in East Africa (Uganda and Tanzania). Round 2 surveys were completed by November 2003 with four new countries added: Kenya, Senegal, Cape Verde and Mozambique. Round 3 surveys were conducted from March 2005 to February 2006 in the same countries, plus Benin and Madagascar. The 4th Round of surveys covered 20 countries between 2008 and 2009, with the addition of Burkina Faso and Liberia.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Citizen voice and state accountability: towards theories of change that embrace contextual dynamics - Tembo, Fletcher (Overseas Development Institute, 2012)
The development industry is increasingly pushing practitioners to achieve results, and to do better in demonstrating what works, what does not, and explaining why. There is a growing interest in going beyond the measurement of results to being able to understand the basis for success or failure. Consequently, the development of explicit theories of change (ToCs) is starting to be viewed as central to this process, as a key part of what constitutes ‘rigour’ in impact evaluations. Citizen voice and accountability (CV&A) project interventions produce and reproduce diverse outcomes that are not amenable to linear models of ToCs. This paper uses a critical analysis of CV&A cases from the Mwananchi Governance and Transparency Fund (GTF) programme to examine how citizen voice and accountability happens in different governance contexts. The analytical framework used in this paper draws on the well-known tools of outcome mapping (OM) and political economy analysis (PEA). Key points: Enabling citizens to influence government accountability is a complex process involving political dynamics at the citizens’ interface with state institutions; Developing explicit theories of change (ToCs) from the start of programme planning helps planners delve into complex citizen–state dynamics; and Fusing political economy analysis and outcome mapping tools can help develop a deeper understanding of these dynamics to generate more effective ways to achieve outcomes.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; civil society / sociedade civil